ANALYSIS OF THE DOMINANT FACTORS OF ENVIRONMENTAL RISKS OF ENTERPRISES' ACTIVITIES AND THEIR IMPACT ON THE FINANCIAL CONDITION - FADYEYEVA, Iryna (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article provides a comprehensive analysis of the key environmental risk factors associated with the operation of oil and gas enterprises. It identifies the complex, interrelated nature of these risks and emphasizes that their mutual interaction and cumulative effect significantly influence the financial sustainability and overall stability of such enterprises. Particular attention is given to how these environmental risks evolve within the context of modern production processes and how they affect various organizational and technical aspects of industrial operations. To better understand and manage these risks, the authors have conducted a detailed study of the dominant environmental factors, which led to the development of a coordinate matrix outlining the probabilities and potential consequences of hazardous events. This matrix serves as the foundation for creating logical functions that help structure and facilitate the internal exchange of information, promoting a unified perception of environmental threats among company personnel and enhancing risk awareness at all levels of management.Furthermore, the article proposes a structured classification system for dominant environmental risks in oil and gas operations, grounded in the ALARP (As Low As Reasonably Practicable) principle. This classification reflects the balance between acceptable risk levels and the practicality of implementing preventive measures, taking into account both material and intangible cost-effectiveness. Through the application of this methodology, the authors were able to identify and prioritize the most critical risk factors from a broad set of environmental threats typical for the oil and gas sector. Among these, the following were highlighted as particularly significant: personnel errors leading to violation of technological parameters, inadequate reliability of energy supply and automation systems, unpredictability of well behavior during initial operations, risk of spontaneous ignition of industrial equipment, and substandard lightning protection systems.By establishing a clear classification and prioritization approach, the proposed framework not only enhances decision-making transparency but also serves as a practical tool for knowledge sharing among industry professionals. This approach supports more effective environmental risk management by ensuring consistent evaluation criteria and communication standards across different operational units. Ultimately, the article contributes to the development of a more resilient environmental risk culture in oil and gas enterprises, aiming for greater sustainability and operational safety.
Keywords: Environmental risk factor; financial condition; coordinate matrix of probabilities; principle of reasonable sufficiency